2013
DOI: 10.1007/s40430-013-0024-z
|View full text |Cite
|
Sign up to set email alerts
|

The perturbation of a turbulent boundary layer by a two-dimensional hill

Abstract: Turbulent boundary layers over flat walls in the presence of a hill are frequently found in nature and industry. Some examples are the air flows over hills and desert dunes, but also water flows over aquatic dunes inside closed conduits. The perturbation of a two-dimensional boundary layer by a hill introduces new scales in the problem, changing the way in which velocities and stresses are distributed along the flow. When in the presence of sediment transport, the stress distribution along the hill is strongly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Franklin and Ayek [19] studied the perturbation of a fully developed turbulent boundary layer by a two-dimensional triangular hill. In their experiments, water flows were imposed over a triangular ripple with sharp edges fixed to the bottom wall of a closed-conduit channel.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Franklin and Ayek [19] studied the perturbation of a fully developed turbulent boundary layer by a two-dimensional triangular hill. In their experiments, water flows were imposed over a triangular ripple with sharp edges fixed to the bottom wall of a closed-conduit channel.…”
mentioning
confidence: 99%
“…The authors found that at the leading edge of the ripple the xy component of turbulent stresses increases to around eight times the value over the plane bed, while the viscous stress remains of the same order of magnitude, indicating that the inner regions of the perturbed flow are not in local equilibrium for the triangular ripple with sharp edges. Franklin and Ayek [19] proposed that the absence of local equilibrium is due to the relatively large ratio between the vertical and longitudinal scales of the flow. However, it could be due to the sharp leading edge, which probably shed vortices for Reynolds numbers above some threshold.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Na indústria, os principais exemplos estão relacionados aos escoamentos sobre rugas no interior de dutos e tubos, como ocorre em oleodutos, em linhas de dragagem e em dutos de esgoto. Existem muitos estudos sobre o assunto (Jackson e Hunt, 1975;Hunt e outros, 1988;Weng e outros, 1991;Belcher e Hunt, 1998;Franklin e Ayek, 2013).…”
Section: Definições Geraisunclassified
“…Para modelar uma perturbação triangular bidimensional, uma pequena forma de fundo de geometria triangular foi fixada na placa de PVC na seção de testes. A forma triangular teve as mesmas escalas das rugas aquáticas (Franklin, 2010(Franklin, , 2011Franklin e Ayek, 2013). A figura 3.5 apresenta um esquema do perfil triangular fixado na placa PVC e suas dimensões em milímetros.…”
Section: Aparato Experimental Para O Escoamento De áGuaunclassified